2005
DOI: 10.1016/j.taap.2004.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Block of voltage-gated potassium channels by Pacific ciguatoxin-1 contributes to increased neuronal excitability in rat sensory neurons

Abstract: The present study investigated the actions of the polyether marine toxin Pacific ciguatoxin-1 (P-CTX-1) on neuronal excitability in rat dorsal root ganglion (DRG) neurons using patch-clamp recording techniques. Under current-clamp conditions, bath application of 2-20 nM P-CTX-1 caused a rapid, concentration-dependent depolarization of the resting membrane potential in neurons expressing tetrodotoxin (TTX)-sensitive voltage-gated sodium (Nav) channels. This action was completely suppressed by the addition of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 42 publications
4
65
2
Order By: Relevance
“…These larger toxins generally do not affect Kv channels (1, 2); if they bind, they are probably too large to fit properly or do not present the required functional group(s) to interact with the (cytoplasmic) gating machinery. Nevertheless, there is a study that reported inhibition of Kv currents in rat dorsal root ganglia neurons by the pacific CTX-1 with an IC 50 around 20 nM (30).…”
Section: Discussionmentioning
confidence: 99%
“…These larger toxins generally do not affect Kv channels (1, 2); if they bind, they are probably too large to fit properly or do not present the required functional group(s) to interact with the (cytoplasmic) gating machinery. Nevertheless, there is a study that reported inhibition of Kv currents in rat dorsal root ganglia neurons by the pacific CTX-1 with an IC 50 around 20 nM (30).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study using mouse taste cells has demonstrated that ciguatoxin (CTX3C) differs from gambierol in that it did not affect voltage-gated K ϩ channels (Ghiaroni et al, 2006). However, these results indicate that the actions of polyether toxins may differ as a function of cellular context inasmuch as ciguatoxin has been shown to inhibit K ϩ currents in dorsal root ganglion neurons (Birinyi-Strachan et al, 2005).…”
Section: Gambierol Antagonism Of Sodium Channelsmentioning
confidence: 96%
“…Studies show that the inhibition of I K can depolarize the cell membrane, prolong AP duration, reduce the amplitude of afterhyperpolarization and lower the threshold for AP firing (Birinyi-Strachan et al, 2005;Safronov et al, 1996), while the inhibition of I A can induce repetitive firing (Amir et al, 2002;Storm, 1988). It is widely accepted that a decrease of VGPCs, including I K and I A , can increase the excitability of cells (Birinyi-Strachan et al, 2005;Yost, 1999).…”
Section: Participation Of Vgpcs In Hypertonicity-induced Nociceptionmentioning
confidence: 99%
“…Studies show that the inhibition of I K can depolarize the cell membrane, prolong AP duration, reduce the amplitude of afterhyperpolarization and lower the threshold for AP firing (Birinyi-Strachan et al, 2005;Safronov et al, 1996), while the inhibition of I A can induce repetitive firing (Amir et al, 2002;Storm, 1988). It is widely accepted that a decrease of VGPCs, including I K and I A , can increase the excitability of cells (Birinyi-Strachan et al, 2005;Yost, 1999). Recent evidences suggest that VGPCs participate in nociceptive signal transduction induced by inflammatory mediators (Harriott et al, 2006;Sculptoreanu et al, 2004;Stewart et al, 2003;Takeda et al, 2006;Yoshimura and de Groat, 1999;Xu et al, 2006) and nerve injury (Everill and Kocsis, 1999;Ishikawa et al, 1999;Rasband et al, 2001) in primary sensory neurons.…”
Section: Participation Of Vgpcs In Hypertonicity-induced Nociceptionmentioning
confidence: 99%